EDUKASI PIJAT OKETANI SEBAGAI UPAYA NONFARMAKOLOGI DALAM MENINGKATKAN PRODUKSI ASI PADA IBU NIFAS - Kristin - Natalia; Naimah Nasution; Esterlita Sinuhaji (Jurnal Pengabdian Masyarakat Putri Hijau, 2026)
Optimal breast milk production is very important to support infant growth and development during the early stages of life. However, many postpartum mothers still experience difficulties in breast milk production due to several factors, such as stress, inadequate nutrition, and limited knowledge regarding breast care and proper breastfeeding techniques. One of the non-pharmacological methods that can be used to help increase breast milk production is Oketani massage. Oketani massage is a breast massage technique that can stimulate prolactin and oxytocin hormones, thereby helping to improve breast milk flow and making the breasts softer and more elastic. This Community Service Program (PKM) will be held in Mei 2026 aims to increase postpartum mothers’ understanding of the benefits of Oketani massage and its effect on increasing breast milk production. The method used in this activity consisted of health education and demonstrations of Oketani massage for postpartum mothers. The material was delivered interactively by providing explanations regarding the benefits of exclusive breastfeeding, factors affecting breast milk production, and the correct steps of Oketani massage. In addition, observations were conducted on breast milk production through several indicators, such as breastfeeding frequency, infant urination frequency, infant calmness after breastfeeding, and infant weight gain. The results showed that there was an effect of Oketani massage on breast milk production in postpartum mothers with a ρ-value of 0.001 where ρ < α (0.05), indicating that Oketani massage was effective in increasing breast milk production. Through this activity, it is expected that postpartum mothers will be able to apply Oketani massage independently as a non-pharmacological method to help increase breast milk production, so that infants’ nutritional needs can be optimally fulfilled and support the success of exclusive breastfeeding.